Codex historicus i codzienność misji w Chesterfield Inlet (Igluligaarjuk) w arktycznej Kanadzie, 1912-1917 - ZAJĄC, PAWEŁ (Annales Missiologici Posnanienses, 2010)
Different publications on missions very often use the letters of the missionaries as the source of their elaboration. This article presents vision of everyday life of the missionaries in the Canadian Arctic, precisely in the mission of Chesterfield Inlet (Igluligaarjuk) based on the perspective of the Codex Historicus of given mission. Letters are written not so often as inputs in the Codex, therefore it seems that it is worth initiative to look on missionary life in the Arctic from such a perspective.